A educação linguística e a educação de jovens e adultos - Périco, Ana Gabriela (2009)
Due to the little offer of Portuguese Teaching material for High School Adult groups, it became necessary to research what teachers use in their classes and which curriculum and competences they prioritize. For doing that, a teachers profile was built, through a questionnaire about the material used. This is an exploratory research, more specifically, a case study. Linguistic Education, a subarea of First Language Teaching, has as objective to make the student a polyglot in his own language (Bechara, 1985), for that, bringing together some pedagogical and linguistic knowledge. The first one was extracted from Mathematical Education (Machado et alii, 2002), and the second one, from Functional and Textual Linguistics, besides the four Pedagogies (Antunes, 2003): Conversation, Reading, Writing, and Lexical-Grammar. Evaluation was also taken into consideration. Besides that, a historical development of Adult Education in Brazil was organized, as well as an attentive reading of some official High School Brazilian documents, as Lei de Diretrizes e Bases da Educação Nacional n ° 9394/96, Diretrizes Curriculares Nacionais para o Ensino Médio, Parâmetros Curriculares Nacionais do Ensino Médio, Orientações Educacionais Complementares aos PCN Linguagens, Códigos e suas Tecnologias, and the newest Proposta Curricular do Estado de São Paulo, and Diretrizes Curriculares Nacionais para a Educação de Jovens e Adultos. Fourteen Portuguese Teachers of nine schools in Guarujá, SP, have answered a questionnaire about his academic formation, teaching strategies, as well as the material they use to teach. Some preparatory material for ENCCEJA Exame Nacional para Certificação de Competências de Jovens e Adultos was found, which is very satisfactory, according to the four Pedagogies, although it is not used by those teachers. The Apostila was pointed as the material used by part of them, but it was not according to any proposal studied here. An inadequate material in addition to no studies about Adult Education in university show that Linguistic Education, even being object of reflections for more than twenty years, has not arrived in Brazilian classrooms yet